(untitled) (Journal of the College of Education for Women, 2019)
The research talked about one of the important social subject that care public so cities which is .This subject deals with three subdivisions papers :-The first one deals with the reasons of unemployment mentioned the definition of it in addition to make a comparison between it and inertia . then talked specially about unemployment that had got in our wounded country become of wars in it .It had a branch talked about in Islamic society .The second one deals with the negative results of unemployment specially economic , moral and social with their roles in spreading negative phenomenon in our society as terrorist , stolen … etc …The third one deals with the ways of reducing unemployment and trying to limit it , that may achieve under two conditions as crafts unemployment divide the jobs according to purifying in work but it is also spread .Whereas the other one is the ways of unemployment of graduation in IraqThe research had concluded with praying of Mohamad